Մխիթարյանների դերի գնահատումը ժամանակի եւ ազգային հեռանկարի տեսանկյունից - Վաչագան Ավագյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье автор исследует, как именитый литературовед Аршак Чопанян оценивал деятельность Мхитара Себастаци и Мхитаристов. Впервые этот вопрос изучается на основе необходимых сочетаний и параллелей, оставляя в стороне замкнутый и самодовлеющий способ предыдущих исследований. В частности, сравнивая квалификации Чопаняна и предыдущих исследователей Мхитаристов, автор показывает, как суждения Чопаняна верно и обоснованно характеризуют роль и значимость арменофильской деятельности Аббата и основанного им ордена в жизни и истории нашего народа. Сегодня, в 300-летний юбилей Ордена, эти оценки имеют как историческую ценность, так и важную значимость в контексте с научной квалификацией деятельности Ордена. In the article, the author explores how the eminent literary critic Arshag Chobanian assessed the activities of Mekhitar of Sebastia and the Mekhitarists. For the first time, the study reviews the subject on a comparative basis, leaving aside the selfcontained and self-sufficient method of previous studies. In particular, comparing the qualifications of Chobanian and previous researchers about the Mekhitarists, the author shows how Chobanian’s judgments correctly and reasonably characterize the role and significance of the Abbot’s Armenophile activity and of the Congregation he founded in the life and history of our nation. Today, on the 300th anniversary of the Mekhitarist Congregation, these assessments also have both historical value and essential significance in terms of the academic evaluation of the activity of the Congregation.
Keywords: Christianity; History of the Armenian Church